Estudo experimental da associação de Runcinioides argenteus (Araneae, Thomisidae) em Trichogoniopsis adenantha (DC) (Asteraceae) - Romero, Gustavo Quevedo, 1974- (2001)
Orientador : João Vasconcellos Neto